TANGGUNG GUGAT PEMERINTAH DALAM PERLINDUNGAN DATA PRIBADI - Mriya Afifah Furqania; Ahmad Sholikhin Ruslie (Gapenas Publisher, 2023)
This research is meant to find out and explain whether a country or government is sued if it fails to provide protection for personal data. This research uses normative juridical research methods with a statutory approach method and a conceptual approach equipped with two legal materials, namely primary legal materials in the form of laws and regulations and secondary legal materials in the form of books and journal articles. The novelty of this research is the existence of new laws and regulations on personal data protection, namely by using Law Number 27 of 2022 concerning Personal Data Protection. The results obtained from this study are that the state / government is able to be held accountable if it fails to provide protection for personal data. This can be seen from Article 12 of the Personal Data Protection Law which states the rights of personal data subjects, one of which has the right to sue and receive compensation for violations in the processing of personal data. However, the provisions regarding compensation procedures have not been further regulated in the implementing government regulations of the Personal Data Protection Law. The conclusion of this study found that there is a right of citizens to sue and receive compensation other than the Civil Code, the Population Administration Law and the Electronic Information and Transactions Law. This right is born from the fault of the government in the form of unlawful acts by the government or onrechtmatige overheisdaad.